Blockchain, fractional ownership, and the future of creative work - Amy Whitaker; Roman Kräussl (Goethe University Frankfurt, Center for Financial Studies (CFS), 2018)
While record-making prices at art auctions receive headline news coverage, artists typically do not receive any direct proceeds from those sales. Early-stage creative work in any field is perennially difficult to value, but the valuation, reward, and incentivization for artistic labor are particularly fraught. A core challenge in studying the real return on artists' work is the extreme difficulty accessing data from when an artwork was first sold. Galleries keep private records that are difficult to access and to match to public auction results. This paper, for the first time, uses archivally sourced primary market records, for the artists Jasper Johns and Robert Rauschenberg. Although this approach restricts the size of the data set, this innovative method shows much more accurate returns on art than typical regression and hedonic models. We find that if Johns and Rauschenberg had retained 10% equity in their work when it was first sold, the returns to them when the work was resold at auction would have outperformed the US S&P 500 by between 2 and 986 times. The implication of this work opens up vast policy recommendations with regard to secondary art market sales, entrepreneurial strategies using blockchain technology, and implications about how we compensate creative work.
urn:nbn:de:hebis:30:3-468036
Keywords: 330; value creation; art market; property rights; blockchain; venture funding